Psychotherapy and counselling in practice : a narrative framework - Tantam, Digby (Cambridge University Press, 2002)
This important and timely book gives a synthesis, based on actual cases, evidence, practice and experience, to describe the process of psychotherapy and identify the fundamental elements that lead to good outcome across all its varied schools. It is essential reading for anyone working with patients using a psychotherapy model.
Keywords: Psychotherapy.; Psychotherapy -- methods; Counseling -- methods; Psychotherapy; Psychothérapie.; PSYCHOLOGY -- Psychotherapy -- General.; Psychotherapie.; Counseling.; Verteltheorie.